"I have to constantly prove to myself, to people, that I fit the bill": Perspectives on weight and shape control behaviors among low-income, ethnically diverse young transgender women. (September 2016) - Gordon, Allegra R.; Austin, S. Bryn; Krieger, Nancy; White Hughto, Jaclyn M.; Reisner, Sari L.
Abstract: The impact of societal femininity ideals on disordered eating behaviors in non-transgender women has been well described, but scant research has explored these processes among transgender women. The present study explored weight and shape control behaviors among low-income, ethnically diverse young transgender women at high risk for HIV or living with HIV in a Northeastern metropolitan area. Semi-structured in-depth interviews were conducted with 21 participants (ages 18–31 years; mean annual income <10, 000; ethnic identity: Multiracial [n = 8], Black [n = 4], Latina [n = 4], White [n = 4], Asian [n = 1]). Interviews were transcribed and double-coded using a template organizing method, guided by ecosocial theory and a gender affirmation framework. Of 21 participants, 16 reported engaging in past-year disordered eating or weight and shape control behaviors, including binge eating, fasting, vomiting, and laxative use. Study participants described using a variety of strategies to address body image concerns in the context of gender-related and other discriminatory experiences, which shaped participants' access to social and material resources as well as stress and coping behaviors. Disordered weight and shape control behaviors were discussed in relation to four emergent themes: (1) gender socialization and the development of femininity ideals, (2) experiences of stigma and discrimination, (3) biological processes, and (4) multi-level sources of strength and resilience. This formative study provides insight into disordered eating and weight and shape control behaviors among at-risk transgender women, illuminating avenues for future research, treatment, and public health intervention. Highlights: Disordered weight control behaviors have been understudied in transgender women. Societal femininity ideals and pervasive transphobia can interact to heighten risk. Young women described diverse strategies for developing positive body image. Gender affirmation is a valuable framework for promoting transgender health equity.